Meningkatkan Keterlibatan Mahasiswa dan Kompetensi Bisnis Properti melalui Pembelajaran Berbasis Proyek di Perguruan Tinggi - Awaluddin, Awaluddin; Azwar Anas Idris, Andi; Pindasari, Nanang; Ermawati, Elly; Kumalasari, Vita; Afdhal Adiharma, Mohammad; Santrio, Adam; Rahmi Diah Fatmi, Anggun; Mu’min Z., Nurul; Sirniawan, Sirniawan (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2026)
This classroom action research examines the effectiveness of implementing Project-Based Learning (PjBL) to enhance student engagement and competencies in the Property Business course. The research subjects consisted of 28 sixth-semester students of the Entrepreneurship Study Program at ITBM Kolaka in the 2024/2025 academic year. The study was conducted in two cycles, each comprising planning, implementation, observation, and reflection stages. Research instruments included student engagement observation sheets, project report assessment rubrics, and learning process documentation. The results revealed a significant improvement in student engagement, with active participation increasing from 78% in the first cycle to 88% in the second cycle. Analysis of specific project components showed quality improvements in location analysis by 25.8%, cost estimation and Return on Investment (ROI) capabilities by 35.6%, and project report structure by 18.1%. These findings were reinforced by statistical analysis using paired sample t-test, indicating a significant increase in the average score from 3.22 to 4.03 (t(27) = 8.167, p < 0.001). The implementation of PjBL proved effective not only in enhancing conceptual understanding but also in developing analytical, financial, and professional communication skills essential in the property business world.